Evaluation of a didactic intervention in measurement through a pre-experimental design (Edma 0-6: Educación Matemática en la Infancia, 2021)
The present work analyzes the efficiency of a didactic intervention aimed at facilitating the overcoming of difficulties in the learning of the measurement of areas of surfaces and volumes of bodies for Primary Education students, motivated by different types of identified errors. A pre-experimental design is used with 5th grade. Ad-hoc designed pretest and postest were delivered as instruments. To objectify the possible influence of the intervention, an external variable, which was not directly related to the intervention, was used. Despite the limitations of pre-experimental designs, it is concluded that they provide enough information to assess the usefulness of this intervention, to postulate ways of improvement that could guide a future experimental design, or to adopt collaborative research in the classrooms by using meta-analyses.
Keywords: Area; Volume; Learning difficulties; Pre-experimental design; Primary Education